Abortion and contraception practices in COVID-19 era - Maheshwari, Bharti; Manchanda, G. S.; Sharma, Preeti; Setiya, Taniya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: To protect the gains made in sexual and reproductive health in over the past several decades, care for childbearing women and newborn infant’s needs to continue during the pandemic. The provision of safe abortion and contraceptive services remains critical. When staff and services are under extreme stress there is a real risk of increasing avoidable harm. Aim and objectives were to determine the effect of COVID-19 on accessibility and acceptance of contraception and safe abortion care services. Methods: Questionnaire survey was Done among 500 women in 6 months from April to September 2020, on availability and utilization of safe abortion and contraception services during lock down in covid time from patients getting treatment by Department of Obstetrics and Gynecology, Muzaffarnagar Medical College and health care workers (paramedics and others staff) of reproductive age group working in the institute. Results: Majority (56%) of women were in the age group of 20-30 years. 70% of women have access to contraception at present while it was reduced to 60% during lockdown. Most commonly used method was barrier method (70%) followed by OCP’s which they could avail maximum from pharmacy (40%). 65% of women had access to post delivery and post abortion contraception with most common method adopted being injectables, in 3% cases IUCD was inserted, 1% ligation with LSCS. Among them 42 cases were covid positive who underwent caesarean section and adopted contraception thereafter with tubal ligation in 2 cases. In this study 32% of women had unwanted pregnancy, among them 35% underwent surgical abortion 61% medical abortion and 4% continued pregnancy. Conclusions: The COVID-19 pandemic has impacted safe abortion and contraception services. Unwanted pregnancy increased to 32%. 62% subjects claimed for accessibility at government centre and door to door by health worker.